2022
DOI: 10.1155/2022/9612296
|View full text |Cite|
|
Sign up to set email alerts
|

Simulation of Mechanical Heart Valve Dysfunction and the Non-Newtonian Blood Model Approach

Abstract: The mechanical heart valve (MHV) is commonly used for the treatment of cardiovascular diseases. Nonphysiological hemodynamic in the MHV may cause hemolysis, platelet activation, and an increased risk of thromboembolism. Thromboembolism may cause severe complications and valve dysfunction. This paper thoroughly reviewed the simulation of physical quantities (velocity distribution, vortex formation, and shear stress) in healthy and dysfunctional MHV and reviewed the non-Newtonian blood flow characteristics in MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 138 publications
(235 reference statements)
0
4
0
Order By: Relevance
“…This is precisely why numerical simulation has emerged as an essential foundation for such optimization, becoming a crucial element in the advancement of medical device research ( Bologna et al, 2023 ) and the assessment of stress-strain patterns in specific pathological conditions within the cardiovascular system ( Di Giuseppe et al, 2021 ). FEM is particularly advanced among numerical simulation tools and has been demonstrated to be highly efficient in modeling PHVs ( Borazjani, 2013 ; Gilmanov and Sotiropoulos, 2016 ; Castravete et al, 2020 ; Lee et al, 2020 ; Chen et al, 2022 ). Furthermore, existing research has demonstrated advanced optimization algorithms that enable the semi-automatic generation and FEM analysis of significant quantities of PHVs, facilitating the selection of optimal candidates among them ( Hsu et al, 2015 ; Li and Sun, 2017 ; Abbasi and Azadani, 2020 ; Gulbulak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is precisely why numerical simulation has emerged as an essential foundation for such optimization, becoming a crucial element in the advancement of medical device research ( Bologna et al, 2023 ) and the assessment of stress-strain patterns in specific pathological conditions within the cardiovascular system ( Di Giuseppe et al, 2021 ). FEM is particularly advanced among numerical simulation tools and has been demonstrated to be highly efficient in modeling PHVs ( Borazjani, 2013 ; Gilmanov and Sotiropoulos, 2016 ; Castravete et al, 2020 ; Lee et al, 2020 ; Chen et al, 2022 ). Furthermore, existing research has demonstrated advanced optimization algorithms that enable the semi-automatic generation and FEM analysis of significant quantities of PHVs, facilitating the selection of optimal candidates among them ( Hsu et al, 2015 ; Li and Sun, 2017 ; Abbasi and Azadani, 2020 ; Gulbulak et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tese investigations have revealed that the Carreau non-Newtonian model is better at predicting these parameters. Terefore, the Carreau model has been suggested as the most suitable model for blood in various studies [7,14] and will also be used in this study.…”
Section: Introductionmentioning
confidence: 99%
“…By examining the OSI contour for different rheological models, it has been demonstrated that the Carreau non-Newtonian model has a better prediction for OSI and its maximum value [9]. The Carreau model has been proposed as the most appropriate model for blood in several studies [9,30,31], which will also be used in this study.…”
Section: Introductionmentioning
confidence: 99%